Combined Use of Biostimulation and Deficit Irrigation Improved the Fruit Quality in Table Grape - Susana Zapata-García; Pablo Berríos; Abdelmalek Temnani; Pedro J. Espinosa; Claudia Monllor; Alejandro Pérez-Pastor (Plants, 2025)
This study aims to determine the effects of four different biostimulation treatments—composed of microorganisms, seaweed, and plant extracts—on the yield and quality traits of table grapes. Those treatments are compared with an untreated control treatment and tested under two different irrigation schedules: (i) Farmer Irrigation (FI), according to farmer criteria, and (ii) a deficit irrigation program, Precision Irrigation (PI), irrigated as FI, except during the post-veraison period when a 10% soil water depletion was allowed to mitigate the lixiviation. The water inputs in the treatments under PI were reduced by 30% without affecting the total yield but still promoting harvest precocity—an effect that was enhanced by the biostimulated treatments. This deficit irrigation program also stimulated berry growth and a higher maturity index. The different biostimulation treatments led to an improvement in the physical and chemical quality traits of the grapes; under FI, they showed a bigger size and a greater weight than the non-biostimulated treatment, while under PI, they showed a higher soluble sugar concentration and maturity index. Regardless of the irrigation program, the commercial berry color proportion was increased in all the biostimulated treatments, reducing the percentage of green berries. The combined use of biostimulation and PI can promote more efficient and sustainable farming practices, promoting fruit yield precocity and quality of the grapevine in drought-prone regions.